Herbal galactogogue supplementation on average zinc and iron levels in breast milk - Pratama, Rini Mustikasari Kurnia; Handayani, Ayu Mustika; Andriani, Lili; Yunus, Ahmad; Novika, Revi Gama Hatta (Intelektual Pustaka Media Utama, 2023)
The problem often encountered concerning failed exclusive breastfeeding is the insight of the mothers into little or less milk production, causing fear of being incapable to satisfy the baby’s needs. The quasi-experimental research design was used in this study. There was a control group and two intervention groups. The intervention group was given moringa leaf extract and banana flower extract for 14 days. Mother’s milk was examined with atomic absorption spectrophotometry (AAS) at Labkesda (regional health laboratory) Jambi Province, Indonesia. Data were analyzed using 1-way- ANOVA. The zinc levels variable in breast milk obtained a p-value of 0.160, indicating that the zinc level in mother’s milk between the control group, moringa leaf extract, and banana flower extract did not show any meaningful difference. The iron levels variable in breast milk obtained a p-value of 0.497, indicating that the Fe levels of mother’s milk in the control group, moringa leaf extract, and banana flower extract did not show considerable distinctions. As a result, zinc and iron levels in the mother’s milk showed no prominent differentiation in the control, moringa leaf extract, as well as banana flower extract groups.